Educator and Student Engagement Relations - Ode Yahyu Herliany Yusuf; Ainna Putri; Wa Harti; Rahmawati Rahmawati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this research is to describe the attachment relationship between educators and students. This research is a library research. Sources of data from books and electronic scientific articles. Data collection techniques by searching for references online through the Google Scholar database. The results of the study in this study indicate that the attachment relationship between educators and students is very important because a good relationship can affect the achievement of students' abilities in various aspects of their development